Investigating Faculty Technological and Pedagogical Content Knowledge: The BiPSU Context - Bentor, Claire Theresa S.; Ceblano, Mae V.; Niez, Roland A. (Future Science / FSH-PH Publications, 2022)
One of the components that shape the educational system is the instructor. They do several tasks at school that significantly impact students' character, value system, principles, and the character of the entire population. Because of the teacher's position in the classroom, the need for teacher professionalism, discipline, competence, commitment, and innovation is crucial for teachers to contribute to the country's educational aim of obtaining an exceptional education. Per the recommendations of the Accrediting Agency of Chartered Colleges and Universities in the Philippines, this study surveyed 31 faculty members in the School of Arts and Sciences department. It evaluated their competency in integrating technology into pedagogical content using Johnson's (2001) cross-sectional descriptive design. Using the updated TPACK (Technology, Pedagogical, and Content Knowledge) instrument developed by Valtonen et al. (2017), the study found that liberal arts faculty understand how various technologies can be used in the classroom. They also recognized that incorporating technology into the classroom may change their teaching. A strong relationship was found between teachers' service length, pedagogical knowledge, sex, and technological knowledge. It was suggested that school administrators prioritize program and investment strategies that develop an experienced teaching workforce of high-quality individuals. It is also advised that the faculty of the School of Arts and Sciences engage in activities that optimize Information and Communication Technology (ICT) to increase their content knowledge, professional growth, and professional learning.